A comparison study of low trauma disclosure participants and their partners - Summers, Kali (Kansas State University, 2015)
Traumatic events affect not only the primary trauma survivor, but also secondary trauma survivors (e.g., spouses, children). Intimate partner relationships provide unique conditions for examining how the interpersonal and/or systemic impact of trauma exposure and post-trauma responses can impact both the primary and secondary trauma survivors, and the interpersonal dynamics of the couple. Preliminary work has indicated that the extent of trauma disclosure may serve as a buffering effect for relationship adjustment for those below the clinical threshold for PTSD (Monk & Nelson Goff, 2014). Researchers also have found that relationships can suffer effects in direct correlation to trauma disclosure (Creech, Benzer, Liebsack, Proctor, & Taft, 2013; Nelson Goff et al., 2006). The current study explored qualitative and quantitative data from low trauma disclosure individuals (n = 15) and their partners. The Couple Adaptation to Traumatic Stress Model (Nelson Goff & Smith, 2005; Oseland, Gallus, & Nelson Goff, in press) was used to provide the framework for understanding the experiences of low trauma disclosure to spouses in a sample of Army soldiers and their spouses. The low trauma disclosure group reported some positive and negative themes related to relationship functioning. The mixed trauma disclosure partners (n = 7) reported primarily negative themes related to relationship functioning, as well as the positive theme of increased communication. The high trauma disclosure partners (n = 4) reported all positive themes related to relationship functioning. Contrary to the original hypothesis, the results indicated mixed trauma disclosure partners seemed to be functioning at lower levels than the low or high trauma disclosure partners A quantitative analysis demonstrated a number of trends throughout the disclosure groups. The low trauma disclosure group reported scores between the mixed and high trauma disclosure groups for all measures. The mixed trauma disclosure group overall reported the highest PTSD scores and lowest couple adjustment scores, despite experiencing the lowest number of traumatic events and general trauma symptoms. The high trauma disclosure group reported the highest couple adjustment scores, despite experiencing the highest number of traumatic events, trauma symptoms, and lowest PTSD scores. Implications for practice and future research also are described.
Keywords: trauma; traumatic stress; military; couples; post traumatic stress disorder; mixed-methods; Communication (0459); Individual & Family Studies (0628); Mental Health (0347); Military Studies (0750); Social Research (0344)